2022
DOI: 10.3390/ijms23158242
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity of Chimeric Antigen Receptor T-Cell (CAR-T) Therapy: Pathophysiology, Clinical Implications, and Echocardiographic Assessment

Abstract: Contemporary anticancer immunotherapy with chimeric antigen receptor T-cell (CAR-T) therapy has dramatically changed the treatment of many hematologic malignancies previously associated with poor prognosis. The clinical improvement and the survival benefit unveiled the risk of cardiotoxicity, ranging from minimal effects to severe cardiac adverse events, including death. Immunotherapy should also be proposed even in patients with pre-existing cardiovascular risk factors, thereby increasing the potential harm o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…However, the more the treatment is used, the more reports highlight some cardiotoxicity effects, potentially related to cytokine release syndrome (CRS), and inflammatory activation is sustained by circulating cytokines, including myocardial injury, tachyarrhythmias, ventricular arrhythmias and atrial fibrillation, myocardial ischemia, and venous thromboembolism [ 50 , 51 ]. CV ultrasound imaging surveillance of subjects treated with CAR-T identified earlier and prevented clinically overt severe cardiotoxicity and cardiovascular complications [ 52 ], as cardiac toxicity related to CAR T-cell-associated CRS may be resolved spontaneously at day-28 post infusion [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the more the treatment is used, the more reports highlight some cardiotoxicity effects, potentially related to cytokine release syndrome (CRS), and inflammatory activation is sustained by circulating cytokines, including myocardial injury, tachyarrhythmias, ventricular arrhythmias and atrial fibrillation, myocardial ischemia, and venous thromboembolism [ 50 , 51 ]. CV ultrasound imaging surveillance of subjects treated with CAR-T identified earlier and prevented clinically overt severe cardiotoxicity and cardiovascular complications [ 52 ], as cardiac toxicity related to CAR T-cell-associated CRS may be resolved spontaneously at day-28 post infusion [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Underlining the importance of prompt identification and management of CAR-T cell toxicity may greatly enhance results and lessen the burden brought on with associated complications. In addition, these tests could confirm whether early action will reduce toxicity without impacting efficacy [95].…”
Section: Treatment and Supportive Carementioning
confidence: 99%
“…Protease inhibitor [37][38][39] Bortezomil/carfezomil CHF/myocardial ischemia/hypertension 1.8-7.2 Endocrinotherapy [40] Goserin/levoprorelin/flutamide/bicalutamide Myocardial infarction/CHF 0.1-5 CART cell therapy [41,42] Tisagenlecleucel/axicabtagene ciloleucel Tachycardia/hypotension/cardiac insufficiency Unclear Arsenic trioxide [43,44] Arsenic trioxide/all-trans retinoic acid Prolonged QT interval/tachycardia 16 Hematopoietic stem cell transplantation [45] Lenalidomide, bortezomib, Isazzomib Arrhythmia/myocardial ischemia/CHF 2-12…”
Section: -34mentioning
confidence: 99%
“…Patients who began taking sacubitril/valsartan in hospital had a lower risk profile for heart failure rehospitalization and cardiovascular death than patients with a delayed initiation of sacubitril/valsartan (8 weeks later) [39] . The clinical trials of sacubitril/valsartan in HFrEF were shown in Table 2 [37][38][39][40][41][42][43][44][45][46][47][48] . LV remodeling was crucial in progression to HFrEF [70] .…”
Section: Sacubitril/valsartan In Heart Failure Reduced Ejection Fractionmentioning
confidence: 99%